Inside SolidWorks / David Murray - Murray, David 1962- (Thomson Delmar Learning, 2006)
Includes features and functions of SolidWorks[registered] 2006. This title marks functionality specific to SolidWorks 2006 for users who have not upgraded to the release. It is packed with the technical content necessary to utilize the software both productively and efficiently.